Backcare awareness among nurses in Hospital Kota Kinabalu - R Ayiesah,; D Ismail, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2007)
Low back pain (LBP) is a major medical and social problem associated with disability and work absenteeism. Since the effect on unawareness on back care among hospital staff may affect the smooth running of the services to the public and patients, it is the objective of this study to identified the awareness of back care among nurses so that preventive measures can be taken. About 80 nurses working in the outpatient clinic was survey using self addressed questionnaires which were adapted from Zutphen Physical Activity Questionnaire at Queen Elizabeth Hospital, Kota Kinabalu. Demographic analysis demonstrated that among the eighty nurses that responded, 37.5% (n=30) are Malays, 25% (n=25) Chinese and 37.5% (n=30) (to include other Sabahan tribes). Their age group varies between 23 to 55 years of age. A total of 72 nurses, both agreed (45%, n=36) and strongly agreed (45% ,n=36) that understanding good postures is important to prevent LBP. They felt strongly (55%, n=44) about the importance of correct lifting techniques, and having a well-designed workplace (50%, n=40). Regarding factors that cause LBP, 55% (n=44) of them strongly agreed that good lifting technique can prevent LBP while 56 (70%) agreed that prolong sitting doing computer work can cause LBP. About 60% (n=48) also agreed that LBP can cause stress and that 45% (n=36) of them strongly agreed that being overweight than average can worsen LBP. However, 40% (n=32) provide a neutral answer to whether height have any influence on LBP while 50% (n=40) agreed that weak back muscles can worsen the backache further. However, 45% (n=36) agreed that games that involved back movement have high risks and 55% (n=44) agreed that swimming helps to strengthen back muscle. The environmental factors addresses issues of footwear and soft mattress where 60% (n=48) agreed while 15% (n=12) strongly agreed that good footware and appropriate use of soft mattresses 60% (n=48) can prevent LBP. This study have demonstrated that the nurses that participated had a clear understanding and knowledge on back care even though a wider study need to be carried out to ensure validity of study finding.